Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1557/jmr.2017.463
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion rare earth nanoparticles functionalized with folic acid for bioimaging of MCF-7 breast cancer cells

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Therefore, a non-metal oxide, Y 2 O 3 nanoparticles have numerous applications in chemical synthesis, mechanical polishing and as additives to drugs, cosmetics, varnishes and food. Y 2 O 3 nanoparticles are gaining interest for application in photodynamic therapy and biological imaging of cancerous cells 79. Also, Gao et al (2019)10 have reported that bone marrow tissue was damaged by Y 2 O 3 nanoparticles’ exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a non-metal oxide, Y 2 O 3 nanoparticles have numerous applications in chemical synthesis, mechanical polishing and as additives to drugs, cosmetics, varnishes and food. Y 2 O 3 nanoparticles are gaining interest for application in photodynamic therapy and biological imaging of cancerous cells 79. Also, Gao et al (2019)10 have reported that bone marrow tissue was damaged by Y 2 O 3 nanoparticles’ exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In detail, A549 cells were incubated with different formulations (with or without BSA pretreatment) for different time intervals. Afterwards, cells were detached and subjected to FCM analysis of intracellular DOX content [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The functionalization with FA ligands was also reported [38], it was done in a Schlenk system in a N2 atmosphere. FA and TEA were added in 10 ml of dry DMSO and they were agitated for 2h at 37°C.…”
Section: Dcnps Synthesis and Functionalizationmentioning
confidence: 98%